2014
DOI: 10.1021/ja504748g
|View full text |Cite
|
Sign up to set email alerts
|

Cation- and Anion-Exchanges Induce Multiple Distinct Rearrangements within Metallosupramolecular Architectures

Abstract: Different anionic templates act to give rise to four distinct Cd(II)-based architectures: a Cd2L3 helicate, a Cd8L12 distorted cuboid, a Cd10L15 pentagonal prism, and a Cd12L18 hexagonal prism, which respond to both anionic and cationic components. Interconversions between architectures are driven by the addition of anions that bind more strongly within a given product framework. The addition of Fe(II) prompted metal exchange and transformation to a Fe4L6 tetrahedron or a Fe10L15 pentagonal prism, depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 92 publications
1
60
0
Order By: Relevance
“…An analogous system in which both cations and anions influence the distribution of several metallosupramolecular products by templation has been described by Nitschke and coworkers 54. In that system a set of cages, helicates and prisms were formed.…”
Section: Discussionmentioning
confidence: 96%
“…An analogous system in which both cations and anions influence the distribution of several metallosupramolecular products by templation has been described by Nitschke and coworkers 54. In that system a set of cages, helicates and prisms were formed.…”
Section: Discussionmentioning
confidence: 96%
“…Riddell et al 70 have continued their work on metallosupramolecular assemblies and have demonstrated anion-driven structural transformations between a number of metal complexed assemblies of the bis-imine formed between 3,3 0 -diformyl-6,6 0 -bypyridine and p-toluidine. This includes the formation of a Cd 10 complex templated by bifluoride (HF 2 À ) ( Figure 48).…”
Section: Self-assembling Systems Involving Anionsmentioning
confidence: 99%
“…Self-assembled receptors or sensors are also capable of selecting guests by an “induced fit” model (10, 11), not just the restrictive lock and key method. The self-assembly of many such complexes has been effected using metal ions (12, 13), small molecules (14), and anions (15, 16). Advancing the use of anions as directing elements and/or templates in self-assembling systems requires an improved understanding of conformational preferences of the flexible receptors comprising these assemblies (5, 8).…”
Section: Introductionmentioning
confidence: 99%